Psychosocial Interventions for Family Carers of People With Dementia: A Systematic Review and Meta-Analysis. (19th January 2020) - Teahan, Áine; Lafferty, Attracta; McAuliffe, Eilish; Phelan, Amanda; O'Sullivan, Liam; O'Shea, Diarmuid; Nicholson, Emma; Fealy, Gerard
Objective: This study aimed to review and synthesize findings of the effectiveness of psychosocial interventions aimed at improving outcomes for family carers of people with dementia.Method: A systematic review and meta-analysis were conducted according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. We systematically searched the following databases: Cochrane, PubMed, Cumulative Index to Nursing and Allied Health Literature (CINAHL), PsycInfo, Excerpta Medica Database (EMBASE), and Applied Social Sciences Index and Abstracts (ASSIA). RevMan 5 software was used to conduct meta-analysis and subgroup analysis using a random-effects model.Results: The search yielded 22 high-quality intervention articles that were suitable for further meta-analysis. Meta-analysis revealed that psychosocial interventions have a small to moderate significant effect on carer burden (standardized mean difference [SMD] = −0.34, confidence interval [CI] = [−0.59, −0.09]), depression (SMD = −0.36, CI = [−0.60, −0.13]), and general health (SMD = 0.34, CI = [0.18, 0.51]).Discussion: Psychosocial interventions had a positive impact on carer outcomes; however, these results should be interpreted with caution, given the significant level of heterogeneity in study designs. Future research could examine contextual and implementation mechanisms underlying psychosocial interventions to develop effective support systems for family carers of people with dementia.